2016
DOI: 10.1111/1462-2920.13418
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of the sensor kinase DcuS of Escherichia coli of the DcuB/DcuS sensor complex to the C4‐dicarboxylate responsive form by the transporter DcuB

Abstract: The sensor kinase DcuS of Escherichia coli co-operates under aerobic conditions with the C -dicarboxylate transporter DctA to form the DctA/DcuS sensor complex. Under anaerobic conditions C -dicarboxylate transport in fumarate respiration is catalyzed by C -dicarboxylate/fumarate antiporter DcuB. (i) DcuB interacted with DcuS as demonstrated by a bacterial two-hybrid system (BACTH) and by co-chromatography of the solubilized membrane-proteins (mHPINE assay). (ii) In the DcuB/DcuS complex only DcuS served as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 48 publications
4
34
0
Order By: Relevance
“…With stronger induction (10 M arabinose), a significant increase (2.5-fold) was observed. These results are in line with data reported earlier (13).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…With stronger induction (10 M arabinose), a significant increase (2.5-fold) was observed. These results are in line with data reported earlier (13).…”
Section: Resultssupporting
confidence: 94%
“…DcuS requires one of the C 4 -dicarboxylate transporters DctA or DcuB for normal function. The transporters form a complex with DcuS, and only the DctA-DcuS and DcuB-DcuS complexes gain responsiveness to the C 4 -dicarboxylates, whereas free DcuS (DcuS F ) is in the permanent "on" state, where signaling occurs independent of C 4 -dicarboxylates (7,(11)(12)(13)15). A model was put forward that suggests two modes of regulation by DcuS (14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DctA therefore clearly acts as an activity switch for DcuS and does not contribute any additional sensory functions to the signalling process. It was recently shown that a functionally equivalent complex is formed between DcuS and DcuB under anaerobic conditions (Wörner et al ., ).…”
Section: Transporters As Activity Switchesmentioning
confidence: 97%